Religion, Motherhood, and the Spirit of Capitalism. (June 2014) - Reynolds, Jeremy; May, Matthew
Religion can help people cope with problems, but in the modern U.S. economy, it may also create problems for some women. Conservative Protestantism encourages women to avoid paid work when they have young children, but that is a preference many families cannot afford. To better understand how workplace outcomes may reflect religion, we examine whether conservative Protestant, mainline Protestant, Catholic, and non-religious women work the number of hours they prefer. We pay special attention to the interplay of religion and motherhood. We find that among new mothers, conservative Protestants are among the most likely to wish they were working fewer hours. Non-religious women, in contrast, are the least likely to want fewer hours. Among women who are not new mothers, the situation is reversed. Conservative Protestants are least likely to wish they were working fewer hours and non-religious women are the most likely to want fewer hours. These results suggest that researchers interested in the subjective side of employment should pay more attention to how religion shapes experiences of paid work.